Performance of nurses/nursing team in the dispensing of materials for users of home care services - Priscila de Carvalho Freitas; Daniel Magno Galdino; Maria de Fátima Grillo; Carmen Lucia Mottin Duro; Êrica Rosalba Mallmann Duarte; Dagmar Elaine Kaiser (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To contextualize the performance of nurses/nursing team in the dispensing of materials to assist users in home visits, in primary care. Methods: Dialectical qualitative study conducted between March and April 2018 in which 24 nurses from primary health care units in the Gloria/Cruzeiro/Cristal District of Porto Alegre, Rio Grande do Sul, completed the self-administered questionnaire, whose data were treated by thematic content analysis. The study was approved by the Research Ethics Committee. Results: Two categories emerged from the empirical corpus: logistic chain of material management for home user assistance; production of services and capacity of the team. Conclusion: The work processes related to materials management for home user assistance and the resulting health services production require a look at specificities such as workload and technologies involved, as they move the performance of the nurse/nursing staff.